PLEOMORPHIC ADENOMA OF MINOR SALIVARY GLANDS - Khan, Mohammad Naeem; Raza, Syed Shahmeer; Zaidi, Syed Aizaz Hussain; Haq, ihtisham ul; Hussain, Amer Kamal; Nadeem, Muhammad Daniyal; Farid, Khayyam (Journal of Ayub Medical College Abbottabad, 2016)
Pleomorphic adenoma is the most common benign tumour of salivary glands which is Known for its wide pleomorphic architecture. It accounts for 45-75% of all salivary gland neoplasm. It can involve major as well as minor salivary glands. Among minor salivary glands (5-10% of cases) the palate lip, nasal cavity, pharynx, larynx and trachea are the most common sites. Diagnosis is made with biopsy along with histopathology. Wide excision with biopsy and removal of underlying extension of tumour is the treatment of choice. Sixty years old farmer presented with painless swelling in the upper lip for the last 8 years. History revealed recurrent mass in the midline of upper lip with no other complaints. He was operated 3 times for this complaint in the past. Belonging to poor socioeconomic status no biopsy records were found. On examination 3Ã—4 cm hard and mobile mass was found. Lymph nodes of head and neck and parotid gland revealed no enlargement. Surgery by wide excision was planned. After baseline investigation surgery was done and the mass sent for histopathology. Biopsy reports showed pleomorphic adenoma on unusual site. Dissection of salivary gland tumour is important as they have propensity to metastasize. Wide local excision along with biopsy is the method of choice. Proper surgical techniques are required to avoid recurrence. Keywords: Pleomorphic Adenoma, Minor Salivary Glands, Recurrent Lip mass